Wax biosynthesis in response to danger: its regulation upon abiotic and biotic stress - Lewandowska, Milena; Keyl, Alisa; Feussner, Ivo (The New phytologist, 2020)
The plant cuticle is the first physical barrier between land plants and their terrestrial environment. It consists of the polyester scaffold cutin embedded and sealed with organic, solvent-extractable cuticular waxes. Cuticular wax ultrastructure and chemical composition differ with plant species, developmental stage and physiological state. Despite this complexity, cuticular wax consistently serves a critical role in restricting nonstomatal water loss. It also protects the plant against other environmental stresses, including desiccation, UVradiation, microorganisms and insects. Within the broader context of plant responses to abiotic and biotic stresses, our knowledge of the explicit roles of wax crystalline structures and chemical compounds is lacking. In this review, we summarize our current knowledge of wax biosynthesis and regulation in relation to abiotic and biotic stresses and stress responses.